2013
DOI: 10.1177/0148607113500695
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Bone Turnover Markers in Children on Long‐Term Parenteral Nutrition (PN) for Intestinal Failure (IF)

Abstract: Bone turnover markers may be useful indicators for identifying children on long-term PN at risk of MBD. Further studies are needed to validate the current results and determine the factors that influence the occurrence and evolution of MBD in children on PN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 42 publications
0
19
2
1
Order By: Relevance
“…This finding comes in contrast to the report by Derepas et al, 10 in which markers of bone turnover in infants with IF and long‐term PN dependence were evaluated. Their study reported no significant difference in BSALP between healthy infants (162.98 ± 39.45 U/L) and infants with IF (184.3 ± 76.25 U/L), but none of the infants with IF had cholestasis or PNALD at the time of evaluation.…”
Section: Discussioncontrasting
confidence: 98%
“…This finding comes in contrast to the report by Derepas et al, 10 in which markers of bone turnover in infants with IF and long‐term PN dependence were evaluated. Their study reported no significant difference in BSALP between healthy infants (162.98 ± 39.45 U/L) and infants with IF (184.3 ± 76.25 U/L), but none of the infants with IF had cholestasis or PNALD at the time of evaluation.…”
Section: Discussioncontrasting
confidence: 98%
“…In the current study, however, we did not find an association between Al concentration and BMD. In a previous study in which we measured osteocalcin (OC) and c‐telopeptide (CTx) in the same group of patients, we found negative correlations between OC, CTx, and BMD 20 . In the present study, failure to see an association between Al concentration and BMD could have been because data on BMD were available for only 16 of the total 27 patients.…”
Section: Discussioncontrasting
confidence: 50%
“…Therefore, suppliers of large‐ and small‐volume parenterals for the Canadian market are not required to provide such information on labels. We have observed that a significant number of our patients receiving long‐term PN (home PN) have metabolic bone disease 20 . We have also observed alteration in calcium and phosphate concentrations as well as suppressed PTH.…”
Section: Introductionmentioning
confidence: 70%
“…Bone turnover markers (osteocalcin, c-telopeptide) may be useful indicators for identifying children on long-term PN at risk of MBD [118] (LOE 2À).…”
Section: Osmolaritymentioning
confidence: 99%